Structural composition and thermal stability of extracted EVA from silicon solar modules waste. (15th November 2020) - Chitra,; Sah, Dheeraj; Lodhi, Kalpana; Kant, Chander; Saini, Parveen; Kumar, Sushil
Graphical abstract: Highlights: A new method is established for the extraction of Ethylene-vinyl acetate (EVA) from the silicon solar modules waste. Recovery of EVA performed by thermal treatment with the application of mechanical force. The structural composition and thermal behaviour of extracted EVA were determined by various analytical treatments. The extracted EVA shows quite similar properties as that of commercial EVA. The use of extracted EVA may be possible in the encapsulation of solar modules and other applications. Abstract: Ethylene-vinyl acetate (EVA), a copolymer of ethylene and vinyl acetate, is widely used as an encapsulant in the silicon solar module to bind the different layers together and protecting the solar cells from over stressing, cracking, and environmental effects. In this work, EVA has been recovered successfully from the used silicon solar module by thermal treatment at 170 °C temperature and the application of mechanical force. The established process is completely environment-friendly, as the EVA layer was recovered without any degradation and emission of any gas. The presence of extracted EVA and its chemical composition was confirmed from FTIR and EDAX measurements. It was observed from Thermogravimetry (TGA) and Differential thermogravimetry (DTG) that thermal degradation of EVA was a two-step process, and also the rate of reaction was fast in an air environment as compared to nitrogen environment. The extracted EVA is thermally stable until 215 °C in the air environment. From Differential scanning calorimetry (DSC) analysis, two endothermic peaks were observed at temperature 37 °C and 55 °C, which may be due to beginning of melting of vinyl acetate and ethylene crystallites respectively in air and nitrogen environment. From UV–visible spectroscopy, it was found that above 500 nm, the extracted EVA is transparent. After examined through the various characterization, it has been observed that extracted EVA shows quite similar properties as that of commercially available EVA. Therefore, the recovered EVA may be used in the encapsulation of solar modules and other applications in packaging and textile industries.